Feed swine in growing and finishing used Alocasia macrorhyza and palm oil (Revista Sistemas de Producción Agroecológicos, 2012)
This research was carried with the purpose of to evaluate the effects of bore (Alocasia macrorhyza) in the diet of grower and finishing pigs on feed intake, gain of weight and ratio intake/gain of weight. The study was carried in Granada, with 24 pigs Pietrain distributed in 4 treatments of two pigs each one, with three repetitions. The treatments were: Control treatment, CT, which corresponds to a commercial nucleus with palm oil; Alocasia macrorhyza to will + nucleus protein of 46.9 crude protein, NPB; Alocasia macrorhyza to will + nucleus protein + 0.1 kg of oil of palm, NPB-AP100 and Alocasia macrorhyza to will + nucleus protein + 0.2 kg oil of palm, NPB-AP200. The levels of Alocasia macrorhyza had effects statistic (P
Keywords: food alternatives; bore; gain of weight; swine